Analyzing the impact of TQM, service quality, and market orientation on customer satisfaction in state-owned banks Indonesia - Arundini, Nabila Kaulika; Sutrisno, Timotius FCW (Universitas Tarumanagara, 2023)
The economic environment has significantly changed, necessitating quality improvements to achieve the organization’s competitive advantage. A notable progress involves the creation and execution of a quality management system, utilizing the Total Quality Management (TQM) principle to address forthcoming consumer requirements. This paper explores the impact of TQM, service quality, and market orientation effects customer satisfaction in East Java’s state-owned banking sector. The researchers collected empirical data from 199 respondents who were employees of state-owned banks in East Java. In this research, we utilized PLS-SEM analysis to investigate the connections between the variables. The results indicate a positive effect between TQM and service quality, market orientation, and customer satisfaction. Moreover, there is a positive association between service quality, market orientation, and customer satisfaction. According to this study, state-owned banks in East Java should focus on implementing TQM, improving service quality, and developing a market orientation to enhance customer satisfaction. By practicing effective TQM, continuously improving service quality, and adapting responsive marketing strategies, state-owned banks can improve customer satisfaction and strengthen their position in the highly competitive banking sector. Lingkungan ekonomi telah mengalami perubahan besar dan perlunya melakukan peningkatan kualitas untuk mencapai keunggulan kompetitif organisasi. Salah satu perkembangan tersebut melibatkan pengembangan dan penerapan sistem manajemen mutu dengan menerapkan konsep Total Quality Management (TQM) guna memenuhi kebutuhan konsumen di masa mendatang. Penelitian ini bertujuan untuk mengeksplorasi pengaruh antara TQM, service quality, dan market orientation terhadap korelasi customer satisfaction di sektor perbankan BUMN Jawa Timur. Peneliti mengumpulkan data empiris dari 199 responden yang merupakan pegawai bank BUMN di Jawa Timur. Dalam penelitian ini, peneliti menggunakan analisis faktor konfirmatori untuk menguji reliabilitas dan validitas konfigurasi, sedangkan hubungan antar variabel diperiksa melalui Partial Least Square. Penelitian ini membuktikan bahwa TQM berhubungan positif dengan Service Quality, Market Orientation, dan Customer Satisfaction. Service Quality dan Market Orientation juga berhubungan secara positif dengan Customer Satisfaction. Menurut penelitian ini, perbankan BUMN di Jawa Timur perlu mendapat perhatian serius untuk menerapkan TQM, meningkatkan kualitas layanan dan mengembangkan orientasi pasar untuk meningkatkan kepuasan nasabah. Dengan menerapkan praktik TQM yang efektif, terus meningkatkan kualitas layanan, dan merespons perubahan strategi pemasaran, perbankan BUMN dapat meningkatkan kepuasan nasabah dan memperkuat posisinya di tengah sektor perbankan yang sangat kompetitif.